2007
DOI: 10.1152/ajplung.00014.2007
|View full text |Cite
|
Sign up to set email alerts
|

CCSP regulates cross talk between secretory cells and both ciliated cells and macrophages of the conducting airway

Abstract: Reynolds SD, Reynolds PR, Snyder JC, Whyte F, Paavola KJ, Stripp BR. CCSP regulates cross talk between secretory cells and both ciliated cells and macrophages of the conducting airway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 47 publications
2
34
0
Order By: Relevance
“…On the basis of this finding and our previous report (215), the authors suggested that "immunomodulatory changes and increases in local production of IgA that are associated with CCSP (UG) deficiency may contribute to systemic organ dysfunction". Consistent with these findings, a recent study using UG (CCSP)-KO mice found that in the conducting airways paracrine signaling between nonciliated secretory cells and cells of the immune system plays a critical role in host defense (225). Furthermore, Yoshikawa et al (226) have proposed that UG may inhibit the cytosolic PLA 2 pathway and reduce lung injury caused by acute high positive inspiratory pressure-induced lung injury.…”
Section: Uteroglobin-knockout Micementioning
confidence: 68%
“…On the basis of this finding and our previous report (215), the authors suggested that "immunomodulatory changes and increases in local production of IgA that are associated with CCSP (UG) deficiency may contribute to systemic organ dysfunction". Consistent with these findings, a recent study using UG (CCSP)-KO mice found that in the conducting airways paracrine signaling between nonciliated secretory cells and cells of the immune system plays a critical role in host defense (225). Furthermore, Yoshikawa et al (226) have proposed that UG may inhibit the cytosolic PLA 2 pathway and reduce lung injury caused by acute high positive inspiratory pressure-induced lung injury.…”
Section: Uteroglobin-knockout Micementioning
confidence: 68%
“…Much of what is available comes from studies of induced lung injury combined with observations of cell population dynamics during recovery (Rawlins et al, 2007). For example, acute airway injury that targets ciliated cells is rapidly resolved through what appears be proliferation and differentiation of Clara cells, thus linking Clara and ciliated cells (Reynolds et al, 2007). Also, in a naphthalene injury model, Clara cells die within the first 24 hours after exposure to this toxicant.…”
Section: Discussionmentioning
confidence: 99%
“…Clara cells are most prominent in the terminal and respiratory bronchioli, but to varying degrees can also be found in larger airways, including bronchi (Broers et al, 1992). As they exhibit the capacity to rapidly repopulate damaged or denuded airway epithelium, Clara cells are presumed to be progenitors for themselves and ciliated cells (Reynolds et al, 2007). Clara cells are thought to be derived from an unknown progenitor in the proximal airways late in lung development [mouse embryonic day 16 (E16)] but the mechanism remains unsubstantiated (Cardoso, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…First, the exact mechanism of action of CC16 is in fact not firmly established here, since ex vivo air-liquid interface cultures of the airway epithelium of knockout mice did not behave differently from the wildtype-derived cells, and demonstrated no exaggerated apoptosis. CC16 may act through a direct intercellular paracrine action [15] or direct inhaled toxicant neutralisation [5], but unfortunately, this was not investigated in the present study. Phospholipase A2 had been considered a possible target for CC16 but this was not confirmed.…”
mentioning
confidence: 89%